Other Undertandsings in Indonesia’s Criminal Law Pottentially Create a Repressive Regime - Al Rasyid, Muhammad Zahid Farhan; -, Mispansyah (Islamic Research, 2025)
The element of “other understanding” in Article 188 of Law Number 1 of 2023 can be considered to violate the principle of legality. Unclear about these types of beliefs and groups that are considered to adhere to these beliefs can lead to many interpretations, contrary to Pancasila. The article is not in line with the criminal law principle of legality or the concept of lex scripta, which emphasizes written and clear provisions in the law. Article 188 is also incompatible with the lex stricta principle because it does not explicitly mention what kind of understanding is meant, causing vagueness and potential abuse of critical activists. Furthermore, other interpretations within Article 188 could also potentially create a repressive regime due to significant restrictions on individual freedoms and rights.